Juridical Review of the Crime of Money Laundering with the Mode of Fried Shares Derived from Corruption Crime (Study of Decision: Number 29/Pid.Sus-Tpk/2020/Pn.Jkt.Pst) - Ari Setiawan (Proceedings Series on Social Sciences & Humanities, 2023)
This study discusses the judge's consideration in making a decision on criminal sanctions for perpetrators of money laundering with the mode of fried stocks originating from corruption (Study of Decision: Number 29/Pid.Sus-TPK/2020/PN.Jkt.Pst.). The writing of this research is motivated by the fact that in cases related to corruption, judges' decisions often do not match the expectations of the community, especially in this case the perpetrators of these crimes play quite beautifully using the proceeds of their corruption to look like legitimate. So from this research it is important to ensure that the decisions that have been given are decisions that are in accordance with the proper regulations so that the public can believe that the law in Indonesia is enforced fairly and efficiently by law enforcers. The type of research in writing this article uses normative juridical research, namely research conducted using the library method by emphasizing the applicable laws and regulations that are relevant to the legal issues that are the focus of the research. The results of the research regarding the application of material criminal law with evidence that has been listed in the decision are in accordance with applicable regulations which refer to Article 2 Paragraph (1) Jo Article 18 of Law Number 31 of 1999 concerning Eradication of Corruption Crimes as amended by Law Number 20 of 2001 concerning amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes Jo. Article 55 paragraph (1) to 1 of the Criminal Code and Article 3 of Law Number 8 of 2010 on the Prevention and Eradication of the Crime of Money Laundering, and Law Number 8 of 1981 on Criminal Procedure and other laws and regulations.